2021
DOI: 10.1088/1612-202x/abf83b
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of polymer composites with nano-titania inclusions

Abstract: This study focuses on the possibility of controlling the morphology, phase-structural transformations, shape and mechanical features of a nano ceramic-polymer matrix by adding nano-titanium dioxide (TiO2) to the polymer during a selective laser sintering process. 3D parts were manufcatured from dissimilar polymers and nano-titania powder compositions with different volume ratios. Evaluations of the microstructural characteristics of the 3D samples were performed using optical and scanning electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recent advancements in additive manufacturing (AM) technologies, commonly referred to as 3D printing, have proven effective in the development of unique structures that can provide proof-of-concept from the desktop to larger industrial-scale designs. Specifically, fused filament fabrication (FFF) 3D printing offers benefits, including low cost, flexibility in feedstock material options, developing proof-of-concept designs that are directly transferable to industrial production, and versatility in joining (adding) materials in unique designs. , The design freedom offered in the 3D print technologies provides substantive benefits to meet the requirements of the unique considerations necessary for photocatalytic treatment design performance (e.g., surface area considerations and density/buoyancy). Recently, pioneering studies have demonstrated the fabrication of a variety of 3D printed TiO 2 composites (e.g., polylactic–hydroxyapatite–TiO 2 ; ceramic–polymer–nano-TiO 2 ; polyetheretherketone (PEEK)–TiO 2 ; polycarbonate (PC)–TiO 2 ). Recent demonstrated uses of AM structures for wastewater treatment included 3D printed polymer–zeolite composite geometries that successfully reduced ammonia concentrations in water and 3D printed polymer–photocatalyst composites having demonstrated proof-of-efficacy for degrading model organic contaminants. , Therefore, there is a strong technical basis for using AM to develop and test potential photocatalytic reactors to provide proof-of-principle performance and optimization that can aid in developing treatment structures that meet the site-specific demands. Additional advantages of incorporating the photocatalyst into a 3D printable polymer includes the ability to augment the density to maintain catalysts in the photoactive zone as buoyant structures to overcome limitations of free powders or “slurries” which would otherwise agglomerate and settle .…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in additive manufacturing (AM) technologies, commonly referred to as 3D printing, have proven effective in the development of unique structures that can provide proof-of-concept from the desktop to larger industrial-scale designs. Specifically, fused filament fabrication (FFF) 3D printing offers benefits, including low cost, flexibility in feedstock material options, developing proof-of-concept designs that are directly transferable to industrial production, and versatility in joining (adding) materials in unique designs. , The design freedom offered in the 3D print technologies provides substantive benefits to meet the requirements of the unique considerations necessary for photocatalytic treatment design performance (e.g., surface area considerations and density/buoyancy). Recently, pioneering studies have demonstrated the fabrication of a variety of 3D printed TiO 2 composites (e.g., polylactic–hydroxyapatite–TiO 2 ; ceramic–polymer–nano-TiO 2 ; polyetheretherketone (PEEK)–TiO 2 ; polycarbonate (PC)–TiO 2 ). Recent demonstrated uses of AM structures for wastewater treatment included 3D printed polymer–zeolite composite geometries that successfully reduced ammonia concentrations in water and 3D printed polymer–photocatalyst composites having demonstrated proof-of-efficacy for degrading model organic contaminants. , Therefore, there is a strong technical basis for using AM to develop and test potential photocatalytic reactors to provide proof-of-principle performance and optimization that can aid in developing treatment structures that meet the site-specific demands. Additional advantages of incorporating the photocatalyst into a 3D printable polymer includes the ability to augment the density to maintain catalysts in the photoactive zone as buoyant structures to overcome limitations of free powders or “slurries” which would otherwise agglomerate and settle .…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques of TDB vary depending on the materials used and the corresponding scaffolding methods. Traditionally, the following biomaterials are applied to form scaffolds [120][121][122][123][124] Additionally, the following techniques are used to create 3D objects [125][126][127][128][129].…”
Section: Bioprinting With the Formation Of Scaffoldsmentioning
confidence: 99%
“…Additionally, the following techniques are used to create 3D objects [ 125 , 126 , 127 , 128 , 129 ].…”
Section: 3d Tissue Bioprintingmentioning
confidence: 99%
“…Moreover, the addition of inorganic fillers in the form of waste into a polymer matrix leads to the formation of the hybrid interfaces, which, in turn, greatly improve the mechanical, physical, thermal, flame retardant, water stability, and durability properties of organic–inorganic (hybrid) composites [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%